Urban and Rural Household Savings in China. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
Household savings behavior in China during the past 30 years has been studied by using econometric models with the time-varying-parameter technique. The rural sector and the urban sector are investigated separately. In comparison to previous studies on the same subject, the estimated models of the current study are more robust, and the results of the models are much more in line with results of similar studies of other countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: China, People's Republic of